2014
DOI: 10.1016/j.agrformet.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Net ecosystem productivity of temperate grasslands in northern China: An upscaling study

Abstract: a b s t r a c tGrassland is one of the widespread biome types globally, and plays an important role in the terrestrial carbon cycle. We examined net ecosystem production (NEP) for the temperate grasslands in northern China from 2000 to 2010. We combined flux observations, satellite data, and climate data to develop a piecewise regression model for NEP, and then used the model to map NEP for grasslands in northern China. Over the growing season, the northern China's grassland had a net carbon uptake of 158 ± 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 85 publications
1
25
1
Order By: Relevance
“…The northeast of the study region (NE) is strongly influenced by temperate monsoon climate, where the rain season occurs in summer (June-August). The annual precipitation is about above 450 mm and the annual mean temperature varies from −3 °C to 9 °C in NE [34]. The altitude was lower than 1000 m and grassland is dominated by meadow steppes.…”
Section: Study Areamentioning
confidence: 99%
“…The northeast of the study region (NE) is strongly influenced by temperate monsoon climate, where the rain season occurs in summer (June-August). The annual precipitation is about above 450 mm and the annual mean temperature varies from −3 °C to 9 °C in NE [34]. The altitude was lower than 1000 m and grassland is dominated by meadow steppes.…”
Section: Study Areamentioning
confidence: 99%
“…To date, significant advances have been made in the upscaling of EC flux observations . A number of studies have upscaled EC flux observations to large regions using satellite remote sensing data and modeling approaches (Xiao et al, 2008(Xiao et al, , 2011aJung et al, 2009;Ryu et al, 2011), and some of these studies have also used the resulting flux estimates to assess regional terrestrial carbon and water budgets (Sun et al, 2011;Xiao et al, 2010Xiao et al, , 2011aZhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…), the type of plant (C3 or C4 metabolism), pasture condition, soil water storage, among others. For example, Zhang et al (2014) showed, in a study of 11 years in temperate grasslands in China, that carbon sequestration occurred, but the ability of the grassland to sequester carbon depended on the type of the pasture and the environmental conditions. In addition, an extreme climate event, such as drought, can significantly reduce carbon sequestration, as observed in periods of lower rainfall and soil water storage ( Figures 1B and 4) in this research.…”
Section: Soil Water Storage (Mm)mentioning
confidence: 99%
“…During the experimental period, the average value of CO 2 fluxes was -0.78 µmol m -2 s -1 , which corresponded to a carbon sequestration of 2.9 t C ha -1 and 8.0 kg C ha -1 d -1 . Several studies (Randow et al, 2004;Wolf et al, 2011;Zhang et al, 2014) have shown that the CO 2 flux values in pastures tend to be negative (i.e., pastures usually act as a sink for CO 2 ).…”
Section: Soil Water Storage (Mm)mentioning
confidence: 99%
See 1 more Smart Citation